Nursing Students' Learning Engagement Experiences During the COVID-19 Pandemic in Namibia: Implications for Nursing Education - Nestor Tomas MPH; Takaedza Munangatire PhD; Sandrina Leila Haita BNSc (SAGE Publishing, 2024)
Introduction Ensuring strong student engagement in both traditional and virtual learning settings was essential for achieving positive educational results during the COVID-19 pandemic. However, fostering student engagement in both the traditional (face-to-face) and virtual learning environments has been accompanied by distinct challenges. There has been a lack of research specifically addressing the issue of nursing students' engagement within a blended learning setting in Namibia. Aim To explore and describe nursing students' learning engagement experiences at a university campus in Namibia during the COVID-19 pandemic. Methods A qualitative, descriptive, phenomenological study was employed to collect data from 10 purposively selected nursing students at a university campus in Namibia. Data from in-depth, face-to-face, individual interviews were collected using a semistructured interview guide. Data were analyzed using Colaizzi's seven-step method. Results The findings of the study describe students' learning engagement experiences under four distinct themes: (a) conditions and contexts of engagement; (b) student acts of engagement: positionality of teacher- and student-facilitated engagement; (c) consequences of engagement in a blended learning environment; and (d) student engagement dispositions: students' initiatives. Conclusion The research findings revealed that despite mental health challenges, both teacher-facilitated and student-facilitated engagement were necessary for positive learning engagement in the blended learning environment. Student-facilitated engagement was significantly responsible for enabling students to maintain focus, adhere to guidelines, and adapt to the blended learning environment. These findings are useful in understanding the challenges faced by students during the COVID-19 pandemic. The findings thus provide valuable data for future studies seeking to address challenges associated with the blended learning environment.